2021
DOI: 10.1007/s42452-021-04513-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites, antibacterial and antioxidant properties of the leaf extracts of Acacia rigidula benth. and Acacia berlandieri benth.

Abstract: The use of plants as sources for novel antimicrobial as well as antioxidant agents offers advantages. Plants are readily accessible and inexpensive, extracts or compounds from plant sources often demonstrate high level of biological activities. Previous studies have reported antibacterial and antifungal activities within the Fabaceae family that included Acacia species. This study aims to determine presence of antibacterial activity, antioxidant activity, and the secondary metabolites of sequential solvent ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Table 2 and graph 2 displayed the average percentages of digestivesystem bacterial-quantity for In-Vivo experiment, it was found Ajwain decreased from the percentage to less than about ten for both uses, it decreased from 61.3% to 4.5% for swallowing and from boiled water extract 61.8% to 3.9%, the percent was decreased but the more effective was the boiled water extract. That found through the result that the use of seeds to drinks and cooking helps to reduce the percentage of bacteria so support individual heath at high-level region [1][2][3][4][5][6][7][8][9][10][11][12][13]. signs were reduced, also by flora, and digestive-system signs, as well that finest by boiled water extract.…”
Section: Globalize Your Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 and graph 2 displayed the average percentages of digestivesystem bacterial-quantity for In-Vivo experiment, it was found Ajwain decreased from the percentage to less than about ten for both uses, it decreased from 61.3% to 4.5% for swallowing and from boiled water extract 61.8% to 3.9%, the percent was decreased but the more effective was the boiled water extract. That found through the result that the use of seeds to drinks and cooking helps to reduce the percentage of bacteria so support individual heath at high-level region [1][2][3][4][5][6][7][8][9][10][11][12][13]. signs were reduced, also by flora, and digestive-system signs, as well that finest by boiled water extract.…”
Section: Globalize Your Researchmentioning
confidence: 99%
“…Which designated the efficiency of the basic mechanisms on the individual health and public health at high-level regions. It indicated the perseverance of the healthy Saudi habits to permanently use seeds to uphold a good state of the digestive system [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Globalize Your Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that all ethanolic extracts had activity against gram-positive bacteria but against Gram-negative bacteria, only leaf and flower fluid extracts showed activity. Cavazos et al determined the antibacterial and antioxidant activity of Acacia berlandieri and Acacia rigidula leaves [9] . Madjid et al investigated the chemical diversity and pharmacological properties of the genus Acacia in 2020 [10] .…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, selected plants showed promising antibacterial activity against P. alcalifaciens, Y. enterocolitica, S. aureus, E. faecalis. Phytochemical analysis was done by different methods such as NMR, IR, UV visible spectroscopy.They have stated that the antibacterial activity of these extracts may be due to the presence of a large number of secondary metabolites 22.…”
mentioning
confidence: 99%